Effects of Exercise Training on Ventricular Remodelling in Patients with Myocardial Infarction: A Systematic Review with Meta-analysis - Tejas R Chokshi; Sohil Takodara; Dinkey Mankad (Journal of Clinical and Diagnostic Research)
Introduction: Ventricular remodelling refers to the process of alteration in ventricular size, shape, and function. It occurs physiologically as a result of exercise or pathologically following cardiac injury and/or abnormal haemodynamic loading conditions. However, the effects of exercise on ventricular remodelling need further investigation. Aim: The aim of the present systematic review was to provide a comprehensive analysis of Exercise Training (ET) interventions for ventricular remodelling in patients with Myocardial Infarction (MI). Materials and Methods: The present systematic review was performed in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-analyses guidelines (PRISMA guidelines). Two independent reviewers completed the title, abstract, and full-text screening for inclusion in the study. Discrepancies were resolved through discussion or by a third reviewer. A literature search was conducted on PubMed, EMBASE, Scopus, PEDRO, Google Scholar, and ResearchGate by two independent investigators using the following keywords: “aerobic exercise,” “strength training,” “ventricular remodelling,” “Left Ventricular (LV) remodelling,” “Randomised Controlled Trials (RCT),” and “MI.” A total of 10 randomised controlled trials were included in the study. All analyses were conducted using RevMan version 5.4.1, following the Cochrane handbook for systematic reviews. For both primary and secondary outcomes, pooled means and Standard Deviations (SD) were extracted along with a 95% Confidence Interval (CI). Results: A total of 10 RCTs were included in the present study combining the data from 550 patients and the mean age of participants was 38 years, ranging from 18 to 65 years. Of the 10 studies, six employed aerobic exercise as an ET intervention, while the remaining four studies included a combination of aerobic and resistance training as an ET intervention. The mean rehabilitation duration was between 3 and 8 months. The majority of studies in this review demonstrated that ET has favourable outcomes in LV end diastolic volume and LV mass. Conclusion: Based on the analysis of the studies included in this review, we can conclude that LV remodelling following MI is enhanced by ET. An early start of ET and a longer duration of up to six months offer more benefits in the recovery of myocardial and LV functions.